An Adaptable, Open-Access Test Battery to Study the Fractionation of Executive-Functions in Diverse Populations - Zanini, Gislaine A. V.; Miranda, Monica C.; Cogo-Moreira, Hugo; Nouri, Ali; Fernández, Alberto L.; Pompéia, Sabine (Frontiers in Psychology, 2021)
The umbrella-term ‘executive functions’ (EF) includes various domain-general, goal-directed cognitive abilities responsible for behavioral self-regulation. The influential unity and diversity model of EF posits the existence of three correlated yet separable executive domains: inhibition, shifting and updating. These domains may be influenced by factors such as socioeconomic status (SES) and culture, possibly due to the way EF tasks are devised and to biased choice of stimuli, focusing on first-world testees. Here, we propose a FREE (Free Research Executive Function Evaluation) test battery that includes two open-access tasks for each of the three above mentioned executive domains to allow latent variables to be obtained. The tasks were selected from those that have been shown to be representative of each domain, that are not copyrighted and do not require special hardware/software to be administered. These tasks were adapted for use in populations with varying SES/schooling levels by simplifying tasks/instructions and using easily-recognized stimuli such as pictures. Items are answered verbally and tasks are self-paced to minimize interference from individual differences in psychomotor and perceptual speed, to better isolate executive from other cognitive abilities. We tested these tasks on 146 early adolescents (aged 9-15 years) of both sexes and varying SES, because this is the age group in which the executive domains of interest become distinguishable and in order to confirm that SES effects were minimized. Performance was determined by Rate Correct Scores (correct answers divided by total time taken to complete blocks/trial), which consider speed-accuracy trade-offs. Scores were sensitive to the expected improvement in performance with age and rarely/inconsistently affected by sex and SES, as expected, with no floor or ceiling effects, or skewed distribution, thus suggesting their adequacy for diverse populations in these respects. Using structural equation modeling, evidence based on internal structure was obtained by replicating the three correlated-factor solution proposed by the authors of the model. We conclude that the FREE test battery, which is open access and described in detail to encourage replication, may be useful for research in a wide range of populations.